2010
DOI: 10.1103/physrevb.81.064432
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of the frustrated spin ladder

Abstract: We re-visit the phase diagram of the frustrated spin-1/2 ladder with two competing inter-chain antiferromagnetic exchanges, rung coupling J ⊥ and diagonal coupling J×. We suggest, based on the accurate renormalization group analysis of the low-energy Hamiltonian of the ladder, that marginal inter-chain current-current interaction plays central role in destabilizing previously predicted intermediate columnar dimer phase in the vicinity of classical degeneracy line J ⊥ = 2J×. Following this insight we then sugge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
93
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 49 publications
5
93
0
Order By: Relevance
“…These values are known to be deep in the CD phase for ferromagnetic couplings. 22,23,25 In Fig. 3(b), we plot the fidelity per lattice site d for the number of initial trial states n. In the CD phase it is clearly observed in the same way that there exist two degenerate ground-states corresponding to the two values of d. In fact, for a large enough number of random initial state trials, the probability P(n) of each degenerate ground-state approaches 1/2, i.e., lim n→∞ P(n) = 1/2.…”
Section: Detecting Non-degenerate Ground-statementioning
confidence: 99%
See 1 more Smart Citation
“…These values are known to be deep in the CD phase for ferromagnetic couplings. 22,23,25 In Fig. 3(b), we plot the fidelity per lattice site d for the number of initial trial states n. In the CD phase it is clearly observed in the same way that there exist two degenerate ground-states corresponding to the two values of d. In fact, for a large enough number of random initial state trials, the probability P(n) of each degenerate ground-state approaches 1/2, i.e., lim n→∞ P(n) = 1/2.…”
Section: Detecting Non-degenerate Ground-statementioning
confidence: 99%
“…18,20 On the other hand, further numerical work provided evidence supporting the existence of the CD phase. 21,22 In particular, the CD phase was claimed to exist in the range 0.373 ≤ J ⊥ ≤ 0.386 for J × = 0.2. 22 This point was further addressed by more extensive density-matrix renormalization group (DMRG) calculations in the range 0.36 ≤ J ⊥ ≤ 0.4 for J × = 0.2, from which it was concluded that the CD phase does not appear.…”
Section: Introductionmentioning
confidence: 99%
“…A large λ ǫ < 0 indicates a staggered dimer order on the 2D lattice while λ ǫ > 0 gives a herringbone dimer structure. Depending on the microscopic couplings, it is also possible for the system to acquire a dimerized or magnetically ordered ground state when one of the marginal couplings λ a or λ b , respectively, reaches first the strong coupling limit [63,64]. Finally, the relevant coupling constant λ c with scaling dimension d c = 3/2 may also become largest, a case where no simple order can be assigned to the 2D system and a spin liquid phase is possible.…”
mentioning
confidence: 99%
“…We now proceed to numerically integrate the RG equations (6) for different lattice parameters until one of the couplings becomes unity [55,64]. The constant Ω in the definition of the initial values in Eq.…”
mentioning
confidence: 99%
“…Frustration can also arise due to competing interactions such coupling (to be discussed later in this chapter), and in spin ladder compounds [39] where frustrated interchain exchange interactions occur both on rungs and diagonals. Since frustration results in multi-degenerate ground states rather than one unique stable one, introduction of very small perturbations or fluctuations in the system cause very novel and exotic phenomena to emerge many of which have not been well explained or understood yet.…”
Section: Frustrationmentioning
confidence: 99%